Pengaruh Mediasi Pemasaran Hijau Terhadap Niat Pembelian Online pada Pembelian Skincare di Indonesia - Husna, Nadiatul; Wardana, Candra Kusuma; Ramadani, Kesha Dewi Nur (Universitas Muhammadiyah Surakarta, 2024)
The increasingly severe global warming that is occurring is encouraging companies to become more environmentally conscious. One significant measure is the creation of environmentally benign products, wherein green marketing serves to cultivate a favorable reputation. The objective of this study is to ascertain the role of green marketing as a mediator in the relationship between attitudes towards green products, green price awareness, Green customer value, and Online green purchase intentions. A quantitative approach was employed in this study, which utilized a purposive sampling method to recruit 172 customers in Indonesia who had previously purchased skincare products Online. Moreover, the data were analyzed using Smart PLS. The results demonstrate that green marketing exerts a direct and indirect influence on green product purchase intention. This study also reveals that marketers must enhance consumer awareness of the benefits and impacts of green products through informative campaigns or advertisements. By leveraging signaling and the Attitude-Behavior-Context (ABC) theory, marketers can cultivate positive attitudes toward green products, thereby strengthening purchase intentions. Moreover, pricing that aligns with the perceived benefits by consumers is crucial to maintaining the purchase intention of green products.